P Perencanaan Struktur Gedung Perkuliahan Dan Aula 7 Lantai - Adib Zamroni, Muhammad; Windarto, Yusuf Arif; Widorini, Trias; Crista, Ngudi Hari (Jurnal Civil Engineering Study, 2023)
To build a new lecture building with adequate and optimal facilities, it is necessary to plan well. It is expected to withstand the impact of earthquake shocks through the formation of ductile inelastic responses in certain selected structural components. The structural planning of this 7-storey lecture and hall building refers to several guidelines, including: Planning Procedures for Structural Concrete Requirements for Building Structures SNI 2847: 2019. And Earthquake Resistance Planning Standards for Building and Non-Building Structures SNI 1726-2019. And Minimum Design Loads and Related Criteria for Buildings and Other Structures SNI 1727: 2020. As well as the Guidelines for Loading Planning for Houses and Buildings (PPPURG 1987). And Specifications for Structural Steel Buildings SNI 1729: 2020. As well as the Indonesian Steel Building Planning Guidelines (PPBBI) SNI 1729: 2020. The structural planning of the 7-storey lecture building and hall in Semarang includes the planning of the upper structure and the lower structure. The upper structure includes planning the roof, beams, columns, and floor plates of the building. While the lower structure includes pile foundation planning. The loadings reviewed for structural element planning are dead loads, live loads, and earthquake loads.